Prognostic value of the systemic inflammation response index in patients with acute ischemic stroke. Issue 6 (19th May 2022) - Zhou, Yaping; Zhang, Yidi; Cui, Mingming; Zhang, Yuming; Shang, Xiuli
Abstract: Objectives: Inflammation plays an essential role in acute ischemic stroke (AIS). Recent studies have recognized the systemic inflammation response index (SIRI) as a useful index to indicate inflammation status and predict the prognosis of multiple diseases. However, the relationship between SIRI and AIS prognosis is unclear. Our study is aimed to investigate the association between SIRI and the prognosis of AIS. Methods: Our study prospectively recruited 287 consecutive patients with first‐ever stroke within 72 h after stroke. Demographic and clinical information was collected at baseline. The functional prognosis was assessed 3 months after AIS using the modified Rankin Scale (mRS). A poor outcome was defined as mRS > 2. SIRI was calculated as neutrophil × monocyte/lymphocyte count. Univariate and multivariate analyses were introduced to identify the association between SIRI and AIS prognosis. Receiver operating characteristic curve and reclassification analyses were used to evaluate the predictive value of SIRI for AIS prognosis. Results: The patients with poor prognosis account for 27.5% of all participants. After fully adjusting for all covariates, each standard deviation increment of SIRI caused 58.9% additional risk for poor prognosis after AIS. When dividing SIRI into quartiles, the fourth quartile had a 6.152 times risk than the first quartile. Moreover, after adding SIRI into established clinical risk factors, AUC showed a significant improvement (0.829 vs. 0.790, p for comparison = .016). Consistently, category‐free net reclassification index (NRI, 0.761, 95% CI: 0.517–1.004, p  < .001) and integrated discrimination index (IDI, 0.093, 95% CI: 0.0512–0.134, p  < .001) confirmed the improvement by SIRI to predict poor prognosis of AIS, Conclusion: SIRI is an independent prognostic indicator for AIS. Elevated SIRI is associated with poor functional outcome of AIS. Our findings suggest the usefulness of SIRI to refine the risk stratification of unfavorable prognosis of AIS. Abstract : The present study investigates the association between SIRI and the prognosis of AIS. Our results demonstrated that elevated SIRI is independently associated with poor functional outcome of AIS, which implicates the usefulness of SIRI to refine the risk stratification of unfavorable prognosis of AIS.